ChemInform Abstract: Ionic Liquid Coated Sulfonated Carbon/Silica Composites: Novel Heterogeneous Catalysts for Organic Syntheses in Water. Issue 45 (23rd October 2014) - Gupta, Princy; Kour, Manmeet; Paul, Satya; Clark, James H.
Abstract According to a recently reported procedure carbon/silica composites are prepared from mixtures of starch and glucose (3:1) and coated with ionic liquid such as [bmim]Br.